2009
DOI: 10.1152/ajpregu.90901.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physiological levels of caffeine on Ca2+ handling and fatigue development in Xenopus isolated single myofibers

Abstract: MC. Effect of physiological levels of caffeine on Ca 2ϩ handling and fatigue development in Xenopus isolated single myofibers. Am J Physiol Regul Integr Comp Physiol 296: R1512-R1517, 2009. First published March 4, 2009 doi:10.1152/ajpregu.90901.2008The purpose of the present study was to determine whether exposure to exogenous physiological concentrations of caffeine influence contractility, Ca 2ϩ handling, and fatigue development in isolated single Xenopus laevis skeletal muscle fibers. After isolation, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
1
11
0
2
Order By: Relevance
“…The rise in resting [Ca 2ϩ ] i following muscle contractions found in the present investigation has also been observed in isolated toad and mouse single muscle fibers from healthy animals (9,44) and is a typical feature of severely fatigued muscle. It was especially interesting that it occurred in the present investigation only in the fast-twitch EDL of diabetic animals, and it did so in the face of increased SERCA protein expression (Fig.…”
Section: In Vivo [Ca 2ϩ ] I Homeostasis and Force Production In Diabesupporting
confidence: 83%
“…The rise in resting [Ca 2ϩ ] i following muscle contractions found in the present investigation has also been observed in isolated toad and mouse single muscle fibers from healthy animals (9,44) and is a typical feature of severely fatigued muscle. It was especially interesting that it occurred in the present investigation only in the fast-twitch EDL of diabetic animals, and it did so in the face of increased SERCA protein expression (Fig.…”
Section: In Vivo [Ca 2ϩ ] I Homeostasis and Force Production In Diabesupporting
confidence: 83%
“…Although those mechanisms underlying impaired SR Ca 2ϩ regulatory functions in fatigued skeletal muscle have not been completely elucidated, there is evidence that metabolic perturbations (e.g., ADP, H ϩ , P i , reactive oxygen species) within the cell affect intracellular Ca 2ϩ ([Ca 2ϩ ] i ) (17,23). The observed rise in resting [Ca 2ϩ ] i during muscle fatigue has been observed in isolated toad (43) and mouse single muscle fiber preparations using a lowfrequency fatigue protocol (12). Our recent study has also demonstrated that the resting level of [Ca 2ϩ ] i is increased after tetanic contractions in the in vivo (i.e., circulation intact) muscle preparation model (47,48).…”
Section: ϩmentioning
confidence: 99%
“…These effects however, occur only at supraphysiological caffeine doses, impractical for humans; have been demonstrated only in animal-based research (Rosser, Walsh, & Hogan, 2009), and subsequently have been discounted in relation to anaerobically based exercise (Astorino & Roberson, 2010).…”
Section: Downloaded By [New York University] At 23:26 04 November 2014mentioning
confidence: 99%